Assessment of Possibilities of Using Local Renewable Resources in Road Infrastructure Facilities—A Case Study from Poland - Agnieszka Stec; Daniel Słyś; Przemysław Ogarek; Kacper Bednarz; Izabela Bartkowska; Joanna Gwoździej-Mazur; Małgorzata Iwanek; Beata Kowalska (Energies, 2024)
The rising demand for water and energy is driving the overuse of natural resources and contributing to environmental degradation. To address these challenges, the focus has shifted to low- and zero-emission technologies that utilize alternative sources of water and energy. Although such systems are commonly applied in residential, commercial, and industrial buildings, facilities along transportation routes generally depend on grid connections. This study aimed to enhance operational independence and reduce environmental impacts by modernizing the Rest Area Stobierna (RAS) along Poland’s S19 expressway, part of the Via Carpatia road. A comprehensive technical, economic, and environmental analysis was conducted using HOMER Pro software (3.18.3 PRO Edition) and a simulation model based on YAS operating principles. The proposed Hybrid Renewable Energy System (HRES) incorporates photovoltaic panels, battery storage, and a rainwater harvesting system (RWHS). Two configurations of the HRES were evaluated, a prosumer-based setup and a hybrid-island mode. Optimization results showed that the hybrid-island configuration was most effective, achieving a 61.6% share of renewable energy in the annual balance, a 7.1-year return on investment, a EUR 0.77 million reduction in Net Present Cost (NPC), and a 75,002 kg decrease in CO2 emissions over the system’s 25-year lifecycle. This study highlights the potential of integrating renewable energy and water systems to improve sustainability, reduce operational costs, and enhance service quality in road infrastructure facilities, offering a replicable model for similar contexts.